2015
DOI: 10.1007/s10597-015-9934-9
|View full text |Cite
|
Sign up to set email alerts
|

“Sometimes What They Think is Helpful is Not Really Helpful”: Understanding Engagement in the Program of Assertive Community Treatment (PACT)

Abstract: This exploratory study recruited a purposive sample of twelve clinical staff from a Program of Assertive Community Treatment (PACT) team in central Virginia to understand the perceptions and experiences related to assertive engagement. The researchers coded the transcribed data initially as twenty-three sub-themes and further refined the data into four overarching themes: characteristics of assertive engagement, PACT engagement strategies and engagement strategies for difficult to engage clients. Further analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 19 publications
1
40
0
Order By: Relevance
“…Despite the focus of the assertive community treatment model on treatment engagement, little is known about which specific elements promote engagement, particularly among homeless individuals. A recent qualitative study with assertive community treatment staff, not focused on those who are homeless, identified the following as primary elements for engaging clients: therapeutic alliance between staff and clients, persistence and consistency, the provision of practical assistance and support rather than a sole focus on medications, the team decision making process, acceptance of clients as they are, and flexibility. A British study of engagement in assertive community treatment compared to community mental health teams, again not specific to homeless individuals, found that the small caseloads and team approach of assertive community treatment facilitated treatment engagement.…”
Section: “Difficult To Engage” Populationsmentioning
confidence: 99%
“…Despite the focus of the assertive community treatment model on treatment engagement, little is known about which specific elements promote engagement, particularly among homeless individuals. A recent qualitative study with assertive community treatment staff, not focused on those who are homeless, identified the following as primary elements for engaging clients: therapeutic alliance between staff and clients, persistence and consistency, the provision of practical assistance and support rather than a sole focus on medications, the team decision making process, acceptance of clients as they are, and flexibility. A British study of engagement in assertive community treatment compared to community mental health teams, again not specific to homeless individuals, found that the small caseloads and team approach of assertive community treatment facilitated treatment engagement.…”
Section: “Difficult To Engage” Populationsmentioning
confidence: 99%
“…Client engagement is described both as a client-owned concept (Wild et al, 2006) as well as a social worker-related construct (George et al, 2015;Petriwskyj et al, 2015).…”
Section: Engagement Theorymentioning
confidence: 99%
“…Other contradictions could lie within each of the activity systems, such as different cultural backgrounds of actor A and actor B; different institutional logics (rules and regulations of the service provider vs family values / 'rules'). Moreover, there could be a reluctance to co-create certain types of services with actor B or to engage with the service provider in the first place (George et al, 2015). Additionally, a past negative experience may have created barriers to further engagement (Higgins and Scholer, 2009).…”
Section: Actor B's Activity Systemmentioning
confidence: 99%
See 2 more Smart Citations